MENINGKATKAN RASA TANGGUNG JAWAB SISWA PADA PELAJARAN PKN DI SMA N 1 PELEPAT ILIR - Juriah Juriah (PAKAR Pendidikan, 2016)
Learning is the important component in order to increase human energy resource. In learning progress, all of element have responsibilty to help each other, so that student can develop all potential that they have. This research is focused on growing student responsibility feeling at PKn subject. Learning progress is done with integrating between individual assignment and explanation of teacher. Individual assignment is given to student in order to give responsibility feeling, whereas explanation of teacher as purpose to foster their confidence, also to increase responsibility feeling. From the research can be concluded that occuring enhancement number of responsibility student to solve every single assignment that is given to them.